Odpowiedź :
a) (x+4)-(3-2x)=(3x+4)-(6+x)
x+4-3+2x=3x+4-6-x
x+2x-3x+x=4-6-4+3
x=-3
b) -(3-x)+(2x+2)=-(1-2x)+(2x-15)
-3+x+2x+3= -1+2x+2x-15
x+2x-2x-2x= -1-15+3-3
-x=-16/:(-1)
x= 16
c) -3(x+2)-2(x+3)=-7
-3x-6-2x-6=-7
-3x-2x=-7+6+6
-5x=5/:(-5)
x=-1
d) 2(2x+5)-3(5+x)=4(x+3)+2(2x+2)
4x+10-15-3x=4x+12+4x+4
4x-3x-4x-4x=16-10-15
-7x=-9/:(-7)
x=1²/₇
e) 4(2x-8)-6(x-4)=2
8x-32-6x+24=2
2x=10/:2
x=5
f) -3(x+2)+2(2x-3)=-7(3-x)+5(1-2x)
-3x-6+4x-6=-21+7x+5-10x
-3x+4x-7x+10x=-16+6+6
4x=-4/:4
x=1
x+4-3+2x=3x+4-6-x
x+2x-3x+x=4-6-4+3
x=-3
b) -(3-x)+(2x+2)=-(1-2x)+(2x-15)
-3+x+2x+3= -1+2x+2x-15
x+2x-2x-2x= -1-15+3-3
-x=-16/:(-1)
x= 16
c) -3(x+2)-2(x+3)=-7
-3x-6-2x-6=-7
-3x-2x=-7+6+6
-5x=5/:(-5)
x=-1
d) 2(2x+5)-3(5+x)=4(x+3)+2(2x+2)
4x+10-15-3x=4x+12+4x+4
4x-3x-4x-4x=16-10-15
-7x=-9/:(-7)
x=1²/₇
e) 4(2x-8)-6(x-4)=2
8x-32-6x+24=2
2x=10/:2
x=5
f) -3(x+2)+2(2x-3)=-7(3-x)+5(1-2x)
-3x-6+4x-6=-21+7x+5-10x
-3x+4x-7x+10x=-16+6+6
4x=-4/:4
x=1
(x+4)-(3-2x)=(3x+4)-(6+x)
x+4-3+2x=3x+4-6-x
x+2x-3x+x=4-6-4+3
x=-3
-(3-x)+(2x+2)=-(1-2x)+(2x-15)
-3+x+2x+2=-1+2x+2x-15
x+2x-2x-2x=-1-15+3-2
-x=-15\*(-1)
x=15
-3(x+2)-2(x+3)=-7
-3x-6-2x-6=-7
-3x-2x=-7+6+6
-5x=5
x=-1
2(2x+5)-3(5+x)=4(x+3)+2(2x+2)
4x+10-15-3x=4x+12+4x+4
4x-3x-4x-4x=12+4-10+15
-7x=21
x=-3
4(2x-8)-6(x-4)=2
8x-32-6x+24=2
8x-6x=2+32-24
2x=10
x=5
-3(x+2)+2(2x-3)=-7(3-x)+5(1-2x)
-3x-6+4x-6=-21+7x+5-10x
-3x+4x-7x+10x=-21+5+6+6
4x=-4
x=-1
x+4-3+2x=3x+4-6-x
x+2x-3x+x=4-6-4+3
x=-3
-(3-x)+(2x+2)=-(1-2x)+(2x-15)
-3+x+2x+2=-1+2x+2x-15
x+2x-2x-2x=-1-15+3-2
-x=-15\*(-1)
x=15
-3(x+2)-2(x+3)=-7
-3x-6-2x-6=-7
-3x-2x=-7+6+6
-5x=5
x=-1
2(2x+5)-3(5+x)=4(x+3)+2(2x+2)
4x+10-15-3x=4x+12+4x+4
4x-3x-4x-4x=12+4-10+15
-7x=21
x=-3
4(2x-8)-6(x-4)=2
8x-32-6x+24=2
8x-6x=2+32-24
2x=10
x=5
-3(x+2)+2(2x-3)=-7(3-x)+5(1-2x)
-3x-6+4x-6=-21+7x+5-10x
-3x+4x-7x+10x=-21+5+6+6
4x=-4
x=-1